2016
DOI: 10.1098/rsif.2016.0258
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity, synchronization and persistence in pre-vaccination measles

Abstract: We investigate the relationship between periodicity, synchronization and persistence of measles through simulations of geographical spread on the British Isles. We show that the establishment of areas of biennial periodicity depends on the interplay between human mobility and local population size and that locations undergoing biennial cycles tend to be, on average, synchronized in phase. We show however that occurrences of opposition of phase are actually quite common and correspond to stable dynamics. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Our findings are similar in many aspects to the ones obtained for the case of measles and, more in general, for a SIR model with vital dynamics and external introductions [27,49,28,30,31,23,24,47,50,51]. This exemplifies that different mechanisms of susceptible replenishment can lead to common dynamical features.…”
Section: Resultssupporting
confidence: 87%
“…Our findings are similar in many aspects to the ones obtained for the case of measles and, more in general, for a SIR model with vital dynamics and external introductions [27,49,28,30,31,23,24,47,50,51]. This exemplifies that different mechanisms of susceptible replenishment can lead to common dynamical features.…”
Section: Resultssupporting
confidence: 87%
“…Experiments on the effects of migration between metapopulations, i.e. similar populations but spatially separated, subjected to temporal fluctuations have shown that pathogen prevalence is greatly influenced by the nature of the fluctuation 23 , highlighting the interplay between synchronization and pathogen prevalence in epidemics 24 .…”
Section: Introductionmentioning
confidence: 99%
“…We estimate the movement of individuals within each country using the Radiation Model [24, 25] fitted on commuting data. Individual have a set of preferred locations, with an associated frequency of visit, which is assigned at the start of the simulation based on the fluxes between grid elements estimated by the radiation model [26, 27]. Each day a destination is chosen for each individual among his set of preferred locations according to their frequency of visit, and the individual is moved to that preferred location where it participates to the dynamics of that cell for a duration corresponding to the average work day.…”
Section: Methodsmentioning
confidence: 99%
“…Our simulation model uses grid elements as basic areal units, thus we identified the grid cells corresponding to the different national subdivisions specified by the commuting matrices, and calculated the corresponding aggregated fluxes. These fluxes depend on the fraction of the population participating in the global commuting between regions which is a model parameter [26, 27]: the optimal value was identified by maximizing the common part of commuters – a measure of similarity of flow estimates based on the Sørensen index [29, 30, 31]. Further details are available in the Supplementary Material SM-1.…”
Section: Methodsmentioning
confidence: 99%